Superando os fatores que dificultam a operacionalização da sistematização da assistência de enfermagem: experiência de enfermeiros em um serviço de obstetrícia - Medeiros, Ana Lucia de (2011)
INTRODUCTION: the nursing care systematization NCS applied by the nursing process represents a basic methodology in the planning and performance at the nursing caution. The nursing process is a method used by nurses to collect data, to plan, to implement and to evaluate the caution. OBJECTIVE: the study aims to understand, through the nurses discourse, the factors that make the operationalization of the NCS difficult in an obstetrics public service. METHODOLOGY: the symbolic interactionism and the theory based on data (grounded theory) were used as theoretical and methodological foundation in order to attain the proposed objective. The population was constituted by thirteen nurses who work in a public maternity ward in João Pessoa, Paraíba, Brazil. The nurses were questioned according to the theoretical sampling procedures. RESULTS: some literary texts involving political, social and organizational aspects were used to endorse the discussions. The data analysis resulted in the central category Overcoming the factors which complicate the NCS operationalization through the comprehension that it is an organizational working method and it is able to direct the nursing process. It is also able to promote the care quality, the autonomy, the visibility and the security. The process was constituted by the integration of the categories in the paradigm model by Strauss and Corbin. This resulted in two phenomena: Pointing at the factors that complicate the NCS oparationalization and the ways to a greater adhesion and success through the application of the nursing process ; Realizing the NCS as a working method which organizes, directs and improves the care quality, bringing visibility and promoting security to the nursing team . In this process the nurses showed the knowledge dimension of the NCS experienced as well as their expectations of the socio-organazational context which they make part. CONCLUSION: it may be concluded that the nurses see the NCS as an instrument of theoretic-practical articulation and they identify that the use of this method leads to personal care, based on individual necessities. Besides, there are some positive aspects: it documents the nursing actions in an organized way; it provides security to the client about the provided nursing care; it supplies security to the multiprofessional team because the actions are registered in the client record; it facilitates the care permanence, reflecting a better profession recognition; it generates professional satisfaction which increases the bond between the nurse and the user.